The Effect of Residence in Coastal Areas and Industrial Area on the Occurrence of Type 2 Diabetes Mellitus - Widyananda, Honesty Trisna; Romadhon, Yusuf Alam (Newinera Publisher, 2024)
In Kendal Regency, the prevalence of Diabetes mellitus reached 2.8% in 2021, higher than the average for Central Java province. An unhealthy lifestyle in coastal areas, including lack of physical activity and consumption of foods high in sugar, as well as exposure to air pollution, has the potential to increase the risk of type 2 diabetes mellitus. Previous studies have shown a relationship between environmental factors and the risk of type 2 diabetes mellitus, but the results have varied. This study aims to explore the effect of residence in coastal areas and industrial areas on the incidence of type 2 diabetes mellitus in Kendal Regency. With a deeper understanding of these factors, it is hoped that methods can be obtained to prevent and overcome type 2 diabetes mellitus in the area. This study was to analyze the effect of proximity to the beach and industrial areas on the incidence of type 2 diabetes mellitus in Kendal Regency. This study used observational analytics with a cross-sectional research design. The sampling technique used was purposive sampling. Univariate and bivariate analysis used the Chi-Square test. Significant results were obtained based on the Chi-Square test on the effect of residence in coastal areas and industrial areas on the occurrence of type 2 diabetes mellitus with a p-value of 0.000 ( p-value <0.05). This study shows the effect of proximity to the beach and industrial areas on the incidence of diabetes mellitus in Kendal Regency.